Risk factors for socially dangerous actions in patients with paranoid schizophria - L. A. Ivanova; E. E. Tuaeva; N. Yu. Rozhkova (Acta Biomedica Scientifica, 2025)
Background. The definition of risk factors for dangerous actions in mental disorders is relevant in psychiatry. The aim. Study of risk factors for socially dangerous actions (SDA) in patients with paranoid schizophrenia. Materials and methods. Clinical-psychopathological, clinical-anamnestic, and psychometric (PANSS scale) methods were used. The study examined male patients (average age 41.3 ± 12.8 years) with paranoid schizophrenia, an episodic type of course, undergoing compulsory inpatient treatment. Results. In 72.7 % of cases, SDA was committed by patients under the influence of psychotic experiences with hallucinatory-delusional (22.7 %), delusional (50 %) syndromes, in 27.3 % of cases – with negative symptoms and severe behavioral disorders. Minor injury to health and crimes against persons unknown to patients were more common in the group with negative symptoms (p = 0.042 and p = 0.012, significant differennces – s.d.), рpatients with delusional syndrome were s.d. more likely to be single (p = 0.035). The accentuation of the emotionally unstable type, alcohol consumption, and psychoactive substances were s.d. more common in patients with negative symptoms (p = 0.008, p = 0.011); alcohol dependence syndrome, of the middle stage, with a hallucinatory-delusional seizure structure (p = 0.042). According to the PANSS scale, in the group with hallucinatory delusional syndrome, s.d. among positive syndromes was 71.4 %. In patients with delusional syndrome and negative symptoms, the reliability among negative syndromes was 71.4 % and 51.7 %, respectively. Conclusions. Identification of risk factors for the formation of socially dangerous actions in patients with schizophrenia helps to prevent dangerous actions.